2006
DOI: 10.1002/ange.200602030
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Absolute Stereochemistry of Polygalolides A and B

Abstract: In 2003, Wei and co-workers reported the isolation and structural elucidation of the polygalolides A (1) and B (2) obtained from Polygala fallax Hemsl., a medicinal plant from which extracts are used as tonics and antihepatitis drugs in China.[1] The structure and relative configuration of the polygalolides were determined on the basis of NMR spectroscopic data. However, the issue of the absolute stereochemistry of the molecules has not been resolved. The structural complexity of these molecules, which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The reaction of 2,2,2-trichloroethyl ester 1a in the presence of 10 mol% PtCl 2 and 40 mol% 1,5-hexadiene in toluene at 25 8C gave (Z)-2a, which was derived from the transaddition of the acetal C À O bond to the alkynyl moiety, in 84% yield with exclusive Z stereoselectivity (entry 1). Interestingly, the reaction of substrates 1a, 1b, 1c, and 1d having an electron-deficient ester group afforded Z isomers as the major product (entries 1-4), while the reaction of substrates having a relatively electron-rich ester, such as 1f, 1g, and 1h, proceeded slowly to give the E isomers, which were derived from the formal cis-addition of the acetal C À O bond (entries [6][7][8]. Particularly, the reaction of phenyl ester 1h gave (E)-2h in good yield with exclusive E stereoselectivity (entry 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of 2,2,2-trichloroethyl ester 1a in the presence of 10 mol% PtCl 2 and 40 mol% 1,5-hexadiene in toluene at 25 8C gave (Z)-2a, which was derived from the transaddition of the acetal C À O bond to the alkynyl moiety, in 84% yield with exclusive Z stereoselectivity (entry 1). Interestingly, the reaction of substrates 1a, 1b, 1c, and 1d having an electron-deficient ester group afforded Z isomers as the major product (entries 1-4), while the reaction of substrates having a relatively electron-rich ester, such as 1f, 1g, and 1h, proceeded slowly to give the E isomers, which were derived from the formal cis-addition of the acetal C À O bond (entries [6][7][8]. Particularly, the reaction of phenyl ester 1h gave (E)-2h in good yield with exclusive E stereoselectivity (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the platinum-catalyzed reaction of 1h using 1,5-hexadiene as the olefin ligand gave E-2h as the major product, while that using 1,5-cyclooctadiene produced mainly the Z isomer. Lewis acidic transition metal-catalyzed cyclization of ortho-alkynylanilines, [3,4] ortho-alkynylphenyl ethers, [3a,b,5,6] and ortho-alkynylphenyl sulfides [7] having a carbon migrating group (CR 3 ), such as allyl, acyl, p-methoxyphenyl (MPM), or a-alkoxylalkyl group, attached to the heteroatom (Y), which proceeds through carbon-heteroatom bond addition, was developed for the synthesis of 2,3-disubstituted indoles, benzofurans, and benzothiophenes [Scheme 1, Eq. (2)].…”
mentioning
confidence: 99%
“…While the carbonyl ylide cycloaddition methodology with rhodium( II ) catalysts is rapidly becoming recognized as a powerful means for the construction of highly substituted oxygen‐containing polycycles, a limited number of examples of the successful application of this chemistry to the complete, total synthesis of natural products, especially in optically pure form, have been reported to date 19c,j,n,o. The present synthesis attests to the power and vitality of the tandem reaction sequence in natural product synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent carbodemetalation of the resulting vinylplatinum intermediate 4 involved the 1,3-migration of the α-alkoxyalkyl group on the oxygen atom to give benzofuran 3. This methodology was successfully extended to the synthesis of other heteroarenes such as indoles, [16] benzo[b]thiophenes, [17] and benzo[b]selenophenes (Scheme 5). [18] Moreover, we also demonstrated that the migrating group can be composed of various carbon-based functional moieties, including α-alkoxyalkyl (acetal), acyl, allyl, p-methoxyphenylmethyl, α-phenethyl, ester, or carbamoyl groups, and also various heteroatom-based functional groups, such as sulfonyl and silyl groups, which would lead to intramolecular heteroatom-heteroatom addition reactions.…”
Section: How Did We First Encounter O-propargylic Oximes?mentioning
confidence: 99%